The Issues of Second Layer Charging Fee in Wakalah Takaful Model Practices - Isa, Mohamad Yazid; Abd. Rahim, Ahmad Khilmy; Mohamed Naim, Asmadi; Haji Wahab, Muhammad Zarunnaim (International Review of Management and Marketing, 2017)
This paper aims to examine the issues of second layer of charging fee in the wakalah takaful models practices in Malaysia. Hence, to make sure all the objectives are answered progressively, qualitative research methodology is advocated. The main data were collected from the interview session among scholars and expertise in takaful field. Then, the data has been analysed based on certain coding and themes. In overcame the second layer of charging fee issue, Takaful Operator (TO) should provide a clear contract that been used in their operations. Besides, another approach is by providing concrete decision from the authority body such as from Shariah Advisory Council (SAC). The issue also can be mitigate through a good Shariah framework from takaful operator itself. This study can be expanded by focusing on the issue of customers’ preferences in the selection of takaful products. Besides, the future research can also examine whether these issues attributed to its low market penetration in Malaysia. Keywords: Business administrative, Wakalah takaful model, issue in wakalah model. JEL Classifications: G22, M1